Transparent flexible bi-crosslinking silicon-based modified cellulose aerogel and preparation method thereof

By using vinyl silane, methyl silane and cellulose as raw materials, the preparation of bi-crosslinked silicon-based modified cellulose aerogels is solved, and the application of cellulose aerogels is limited in the fields of heat insulation and insulation is achieved. It has high strength, low thermal conductivity, good hydrophobicity and high light transmittance, suitable for thermal insulation and heat insulation, and has the characteristics of green and environmental protection.

CN119463276AActive Publication Date: 2025-02-18HUBEI XINGRUI SILICON MATERIAL CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411521910.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-29
Publication Date
2025-02-18
Estimated Expiration
2044-10-29

AI Technical Summary

Technical Problem

The application of existing cellulose aerogels in the fields of heat insulation, insulation, adsorption, purification, etc. is limited by the heat resistance and hydrophilicity of cellulose itself, and its hydrophobic properties, flexibility and transparency are insufficient.

Method used

Bi-crosslinked silicon-based modified cellulose aerogel was prepared by using vinyl silane and methyl silane and cellulose as raw materials. The method includes free radical polymerization, hydrolysis-polycondensation reaction, aging and supercritical drying, etc., to form aerogel film with high transparency, good hydrophobicity and high flexibility.

Benefits of technology

It realizes transparent flexible dual crosslinked silicon-based modified cellulose aerogel with high strength, low thermal conductivity, good hydrophobicity and high light transmittance. It is suitable for the field of thermal insulation and thermal insulation, and has the characteristics of green and environmental protection.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119463276A_ABST
    Figure CN119463276A_ABST
Patent Text Reader

Abstract

The invention provides transparent flexible bi-crosslinking silicon-based modified cellulose aerogel and a preparation method thereof.Vinylsilane and methylsilane serve as precursors, polysiloxane homogeneous sol is prepared in a free radical polymerization / hydrolytic polycondensation bi-crosslinking mode, then cellulose gel is immersed in the homogeneous sol, and finally the transparent flexible bi-crosslinking silicon-based modified cellulose aerogel is obtained through a supercritical drying process. The aerogel disclosed by the invention is prepared. Due to a double-crosslinking structure of free radical polymerization and hydrolytic polycondensation, the aerogel has good transparency and strength, and meanwhile, due to introduction of methylsilane and unique characteristics of cellulose, the aerogel is endowed with good hydrophobic performance and excellent flexibility. In addition, the aerogel material has an extremely low heat conductivity coefficient, and the thermal insulation performance is far better than that of a traditional thermal insulation material, so that the aerogel material has a wide application prospect in the fields of thermal insulation and transparent glass.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of aerogel materials and relates to a transparent flexible double-crosslinked silicon-based modified cellulose aerogel and a preparation method thereof. Background Art

[0002] Cellulose is a natural linear macromolecule with a wide range of sources and is renewable, and is recognized as a green biomaterial. At the same time, aerogels prepared from cellulose have attracted widespread attention in the fields of heat insulation, thermal insulation, adsorption, purification, etc. due to their renewability, biodegradability, environmental friendliness, high transparency and good flexibility.

[0003] The practical application of cellulose aerogel is mainly limited by the heat resistance and hydrophilicity of cellulose itself. In order to better play the unique advantages of cellulose aerogel, the surface modification technology of cellulose aerogel has always been a research hotspot.

[0004] Patent CN117126449A discloses a silicon-based modified cellulose aerogel, and its preparation method includes the following steps: adding cellulose to an ionic liquid, heating and stirring, placing the cellulose sol in a vacuum drying oven for vacuuming and degassing to obtain a treated cellulose sol; then preparing the treated cellulose sol into a cellulose sol film by a film-forming process; then adding an ionic liquid aqueous solution to the cellulose sol film to regenerate a cellulose wet gel film; obtaining a cellulose alcohol gel film after solvent replacement; placing the cellulose alcohol gel film in a silica sol solution and allowing it to stand to obtain a cellulose / silicon dioxide composite wet gel film; placing it in an oven for aging to obtain a cellulose / silicon dioxide composite alcohol gel film; finally, supercritically drying the composite alcohol gel film to obtain a flexible and transparent silicon-based modified cellulose aerogel film with a thickness of 0.1-0.5 mm. The silicon-based modified cellulose aerogel has high transparency, but its flexibility and hydrophobic properties need to be further improved.

[0005] Patent CN111499919A discloses a biomass fiber hybrid polyorganosiloxane aerogel glass, the preparation method of which uses vinyl alkoxysilane as a precursor and introduces biomass cellulose, and is prepared through five process steps: free radical polymerization, hydrolysis and condensation, aging, solvent replacement and drying. The aerogel prepared by this method has high light transmittance and high flexibility, but fails to effectively improve its hydrophobic properties, which greatly limits the application of transparent flexible aerogel in the field of insulating glass.

[0006] The purpose of the present invention is to provide a transparent flexible double-crosslinked silicon-based modified cellulose aerogel in view of the deficiencies in the prior art. The aerogel has high strength, high light transmittance, good hydrophobicity, good flexibility and extremely low thermal conductivity. Summary of the invention

[0007] The purpose of the present invention is to provide a transparent and flexible double-crosslinked silicon-based modified cellulose aerogel and a preparation method thereof, which overcomes the problems of poor thermal insulation performance of existing glass and poor hydrophobicity, low transparency and low flexibility of aerogel. The aerogel prepared by the present invention has good hydrophobicity without affecting transparency and flexibility.

[0008] A transparent and flexible double-crosslinked silicon-based modified cellulose aerogel is prepared from vinyl silane, methyl silane and cellulose as raw materials.

[0009] The viscous liquid obtained by free radical polymerization of vinyl silane is mixed with methyl silane in a mass ratio of (5-10):1 to carry out a hydrolysis-condensation reaction.

[0010] The vinyl silane is one or more of vinyl trimethoxy silane, vinyl triethoxy silane, vinyl methyl dimethoxy silane or vinyl ethyl diethoxy silane.

[0011] The methylsilane is one or more of methyltrimethoxysilane and methyltriethoxysilane.

[0012] The cellulose is one or more of carboxymethyl cellulose, carboxypropyl methyl cellulose or hydroxy cellulose.

[0013] A method for preparing a transparent flexible double-crosslinked silicon-based modified cellulose aerogel comprises the following steps: (1) Preparation of homogeneous sol: A free radical initiator is added to vinyl silane, the reaction system is sealed and replaced with an inert gas, and a transparent viscous liquid is obtained by reaction; methyl silane is added to the viscous liquid, and after sufficient mixing, a solvent, deionized water, and a catalyst are added in sequence to obtain a homogeneous sol, wherein the mass ratio of the viscous liquid to the methyl silane is (5-10):1; Preparation of cellulose alcohol gel film: The cellulose and the ionic liquid are mixed, and the mixture is heated and stirred, vacuum degassed and film-formed in sequence to obtain a cellulose sol film; the cellulose sol film is placed in an ionic liquid aqueous solution for regeneration to obtain a cellulose wet gel film; the cellulose wet gel film is subjected to solvent replacement to obtain a cellulose alcohol gel film; (2) placing the cellulose alcohol gel film obtained in step (1) in a homogeneous sol and allowing it to stand to obtain a cellulose / silicon composite wet gel; and subjecting the composite wet gel to aging and supercritical drying in sequence to obtain a transparent and flexible double-cross-linked silicon-based modified cellulose aerogel.

[0014] The reaction temperature for preparing the viscous liquid in step (1) is 100-140° C. and the reaction time is 4-48 h. The free radical initiator is one or more of di-tert-butyl peroxide, azobisisobutyronitrile or azobisisoheptylnitrile. The molar ratio of vinyl silane to free radical initiator is (5-15):1.

[0015] The solvent in step (1) is one or more of methanol, ethanol, n-butanol or tert-butanol; the catalyst is one or more of tetramethylammonium hydroxide, ammonium fluoride or ammonia water; the molar ratio of methylsilane to solvent, deionized water and catalyst is 1:(1-5):(1-5):(0.01-0.1); the ionic liquid is one or more of EmimCl, EmimBr, EmimF, EmimAc, AmimCl, AmimBr or AmimF, and the mass fraction of the ionic liquid used for regeneration of the cellulose sol film is 20wt%; the cellulose sol film is prepared by mixing cellulose and the ionic liquid in a molar ratio of 1:(30-60).

[0016] The solvent replacement in step (1) is performed once every 12 hours, and the replacement is performed 2-4 times; the aging temperature in step (2) is 40-60° C., and the aging time is 12-48 hours; the supercritical drying is carbon dioxide supercritical fluid drying, the pressure is 5-20 MPa, the temperature is 30-60° C., and the drying time is 24-72 hours.

[0017] A transparent, flexible, double-crosslinked silicon-based modified cellulose aerogel is used in the field of thermal insulation and as a transparent glass interlayer.

[0018] The beneficial effects of the present invention are: The double-cross-linked silicon-based structure prepared using vinyl silane effectively improved the transparency and mechanical strength of cellulose aerogel. At the same time, the introduction of methyl silane effectively improved the hydrophobicity and flexibility of cellulose, with a flexural strength of 0.28 MPa, a transmittance of 93%, and a contact angle of 138°.

[0019] The transparent flexible double-crosslinked silicon-based modified cellulose aerogel prepared by the present invention has excellent thermal insulation performance and a thermal conductivity as low as 0.02W·(mk) -1 .

[0020] The transparent flexible double-crosslinked silicon-based modified cellulose aerogel prepared by the invention is easily degradable and is a new type of green and environmentally friendly material. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 Actual picture of the transparent silicon-based modified cellulose aerogel prepared in Example 1. DETAILED DESCRIPTION

[0022] The embodiments of the present invention will be described in detail below with reference to examples. The following examples are only used to illustrate the present invention and should not be construed as limiting the scope of the present invention.

[0023] Example 1 Di-tert-butyl peroxide and vinyltrimethoxysilane were added into a reaction kettle, and after nitrogen replacement, the reaction kettle was heated at 125° C. for 6 hours to obtain a transparent viscous liquid, in which the molar ratio of di-tert-butyl peroxide to vinyltrimethoxysilane was 1:10.

[0024] Methyltrimethoxysilane is added to a transparent viscous liquid, and after sufficient mixing, ethanol, deionized water and tetramethylammonium hydroxide are added in sequence to fully mix to obtain a homogeneous sol, wherein the mass ratio of methyltrimethoxysilane to the viscous transparent liquid is 1:10, and the molar ratio of methyltrimethoxysilane to ethanol, deionized water and tetramethylammonium hydroxide is 1:2:3:0.01.

[0025] Carboxymethyl cellulose was added to the EmimCl ionic liquid, heated and stirred at 70°C until the cellulose was completely dissolved to obtain a uniform and transparent cellulose sol, which was then vacuumed and degassed in a 70°C vacuum oven for 1 hour, wherein the molar ratio of carboxymethyl cellulose to the ionic liquid was 1:50. The above cellulose sol was poured into a mold to form a film and allowed to stand, and a 20wt% EmimCl aqueous solution was prepared and poured into the mold. The solution covered the cellulose sol by 2 mm. After gelling, the film was demolded and taken out, and replaced with ethanol in sequence, once every 12 hours, and replaced twice to obtain a cellulose alcohol gel film. The cellulose alcohol film was placed in the prepared homogeneous sol, and soaked while stirring, with the speed controlled at 200r / min. After standing at room temperature for 12 hours, it was aged in a 60°C oven for 12 hours. Finally, the composite gel film was subjected to supercritical carbon dioxide drying, with the temperature controlled at 50°C, the pressure at 10 MPa, the degassing rate at 1L / min, and dried for 48 hours to obtain a 1mm transparent silicon-modified cellulose aerogel film. The actual photo is shown in the figure. Figure 1 shown.

[0026] After characterization, it was found that the composite aerogel film has a flexural strength of 0.22MPa, a light transmittance of 90%, a contact angle of 135°, and a thermal conductivity of 0.021W·(mk) -1 .

[0027] Example 2 Di-tert-butyl peroxide and vinyltrimethoxysilane were added into a reaction kettle, and after nitrogen replacement, the reaction kettle was heated at 125° C. for 6 hours to obtain a viscous transparent liquid, in which the molar ratio of di-tert-butyl peroxide to vinyltriethoxysilane was 1:10. Methyltriethoxysilane is added to a viscous transparent liquid, and after sufficient mixing, ethanol, deionized water and ammonia water are added in sequence to obtain a homogeneous sol after sufficient mixing, wherein the mass ratio of methyltriethoxysilane to the viscous transparent liquid is 1:5, and the molar ratio of methyltriethoxysilane to ethanol, deionized water and ammonia water is 1:2:3:0.01.

[0028] Hydroxycellulose was added to the EmimCl ionic liquid, heated and stirred at 70°C until the cellulose was completely dissolved to obtain a uniform and transparent cellulose sol, which was vacuumed and degassed in a 70°C vacuum oven for 1 hour, wherein the molar ratio of hydroxycellulose to ionic liquid was 1:50. The above cellulose sol was poured into a mold to form a film and allowed to stand, a 20wt% EmimCl aqueous solution was prepared and poured into the mold, the solution was 2 mm above the cellulose sol, and after gelation, it was demolded and taken out, and replaced with ethanol in sequence, once every 12 hours, and replaced twice to obtain a cellulose alcohol gel film. The cellulose film was placed in the previously prepared homogeneous sol, stirred and soaked, and the speed was controlled at 200r / min. After standing at room temperature for 12 hours, it was aged in a 60°C oven for 12 hours, and finally the composite gel film was subjected to carbon dioxide supercritical drying, the temperature was controlled at 50°C, the pressure was 10 MPa, the degassing rate was 1L / min, and it was dried for 48 hours to obtain a 0.8mm transparent silicon-based modified cellulose aerogel film.

[0029] After characterization, it was found that the composite aerogel film has a flexural strength of 0.21MPa, a light transmittance of 88%, a contact angle of 128°, and a thermal conductivity of 0.024W·(mk). -1 .

[0030] Example 3 Azobisisobutyronitrile and vinylmethyldimethoxysilane were added into a reaction kettle, and after nitrogen replacement, the reaction kettle was heated at 125° C. for 6 hours to obtain a viscous transparent liquid, in which the molar ratio of azobisisobutyronitrile to vinylmethyldimethoxysilane was 1:10. Methyltriethoxysilane is added to a viscous transparent liquid, and after sufficient mixing, methanol, deionized water and ammonia water are added in sequence to obtain a homogeneous sol after sufficient mixing, wherein the mass ratio of methyltriethoxysilane to the viscous transparent liquid is 1:5, and the molar ratio of methyltriethoxysilane to methanol, deionized water and ammonia water is 1:2:3:0.01.

[0031] Carboxypropyl cellulose was added to the EmimCl ionic liquid, heated and stirred at 70°C until the cellulose was completely dissolved to obtain a uniform and transparent cellulose sol, which was vacuumed and degassed in a 70°C vacuum oven for 1 hour, wherein the molar ratio of carboxypropyl cellulose to the ionic liquid was 1:50. The above cellulose sol was poured into a mold to form a film and allowed to stand, a 20wt% EmimCl aqueous solution was prepared and poured into the mold, the solution was 2 mm above the cellulose sol, and after gelation, it was demolded and taken out, and replaced with ethanol in sequence, once every 12 hours, and replaced twice to obtain a cellulose alcohol gel film. The cellulose film was placed in the homogeneous sol prepared previously, and soaked while stirring, and the speed was controlled at 200r / min. After standing at room temperature for 12 hours, it was aged in a 60°C oven for 12 hours, and finally the composite gel film was subjected to carbon dioxide supercritical drying, the temperature was controlled at 50°C, the pressure was 10 MPa, the degassing rate was 1L / min, and it was dried for 48 hours to obtain a 1.2mm transparent silicon-modified cellulose aerogel film.

[0032] After characterization, it was found that the composite aerogel film has a flexural strength of 0.17MPa, a light transmittance of 85%, a contact angle of 125°, and a thermal conductivity of 0.026W·(mk) -1 .

[0033] Example 4 Di-tert-butyl peroxide and vinyltrimethoxysilane were added into a reaction kettle, and after nitrogen replacement, the reaction kettle was heated at 125° C. for 6 hours to obtain a viscous transparent liquid, in which the molar ratio of di-tert-butyl peroxide to vinyltrimethoxysilane was 1:10. Methyltrimethoxysilane is added to a viscous transparent liquid, and after sufficient mixing, ethanol, deionized water and tetramethylammonium hydroxide are added in sequence, and after sufficient mixing, a homogeneous sol is obtained, wherein the mass ratio of methyltrimethoxysilane to the viscous transparent liquid is 1:5, and the molar ratio of methyltrimethoxysilane to ethanol, deionized water and tetramethylammonium hydroxide is 1:2:3:0.01.

[0034] Carboxymethyl cellulose was added to the EmimCl ionic liquid, heated and stirred at 70°C until the cellulose was completely dissolved to obtain a uniform and transparent cellulose sol, which was vacuumed and degassed in a 70°C vacuum oven for 1 hour, wherein the molar ratio of carboxymethyl cellulose to the ionic liquid was 1:50. The above cellulose sol was poured into a mold to form a film and allowed to stand, a 20wt% EmimCl aqueous solution was prepared and poured into the mold, the solution was 2 mm above the cellulose sol, and after gelation, it was demolded and taken out, and replaced with ethanol in sequence, once every 12 hours, and replaced twice to obtain a cellulose alcohol gel film. The cellulose film was placed in the previously prepared homogeneous sol, and soaked while stirring, and the speed was controlled at 200r / min. After standing at room temperature for 12 hours, it was aged in a 60°C oven for 12 hours, and finally the composite gel film was subjected to carbon dioxide supercritical drying, the temperature was controlled at 50°C, the pressure was 10 MPa, the degassing rate was 1L / min, and it was dried for 48 hours to obtain a 1mm transparent silicon-modified cellulose aerogel film.

[0035] After characterization, it was found that the composite aerogel film has a flexural strength of 0.28MPa, a light transmittance of 93%, a contact angle of 138°, and a thermal conductivity of 0.020W·(mk) -1 .

[0036] Comparative Example 1 The same as Example 4, except that the mass ratio of methyltrimethoxysilane to the viscous transparent liquid is 1:1.

[0037] The composite aerogel film has a bending strength of 0.12 MPa, a light transmittance of 80%, a contact angle of 128°, and a thermal conductivity of 0.048 W·(mk). -1 .

[0038] Comparative Example 2 Same as Example 4, except that the cellulose is nanocellulose.

[0039] Characterization revealed that the composite aerogel film had a flexural strength of 0.11 MPa, a light transmittance of 82%, a contact angle of 94°, and a thermal conductivity of 0.038 W·(mk). -1 .

[0040] Comparative Example 3 Same as Example 4, except that methylsilane is replaced by dimethyldimethoxysilane.

[0041] Characterization revealed that the composite aerogel film had a flexural strength of 0.12 MPa, a light transmittance of 79%, a contact angle of 107°, and a thermal conductivity of 0.041 W·(mk). -1 .

Claims

1. A transparent and flexible double-crosslinked silicon-based modified cellulose aerogel, characterized in that: It is made from vinyl silane, methyl silane and cellulose.

2. The transparent flexible double-crosslinked silicon-based modified cellulose aerogel according to claim 1, characterized in that: The viscous liquid obtained by free radical polymerization of vinyl silane is mixed with methyl silane in a mass ratio of (5-10):1 to carry out a hydrolysis-condensation reaction.

3. The transparent flexible double-crosslinked silicon-based modified cellulose aerogel according to claim 1, characterized in that: The vinyl silane is one or more of vinyl trimethoxy silane, vinyl triethoxy silane, vinyl methyl dimethoxy silane or vinyl ethyl diethoxy silane.

4. The transparent flexible double-crosslinked silicon-based modified cellulose aerogel according to claim 1, characterized in that: The methylsilane is one or more of methyltrimethoxysilane and methyltriethoxysilane.

5. The transparent flexible double-crosslinked silicon-based modified cellulose aerogel according to claim 1, characterized in that: The cellulose is one or more of carboxymethyl cellulose, carboxypropyl methyl cellulose or hydroxy cellulose.

6. The method for preparing the transparent flexible double-crosslinked silicon-based modified cellulose aerogel according to any one of claims 1 to 5, characterized in that: The following steps are involved: (1) Preparation of homogeneous sol: A free radical initiator is added to vinyl silane, the reaction system is sealed and replaced with an inert gas, and a transparent viscous liquid is obtained by reaction; methyl silane is added to the viscous liquid, and after sufficient mixing, a solvent, deionized water, and a catalyst are added in sequence to obtain a homogeneous sol, wherein the mass ratio of the viscous liquid to the methyl silane is (5-10):1; Preparation of cellulose alcohol gel film: The cellulose and the ionic liquid are mixed, and the mixture is heated and stirred, vacuum degassed and film-formed in sequence to obtain a cellulose sol film; the cellulose sol film is placed in an ionic liquid aqueous solution for regeneration to obtain a cellulose wet gel film; the cellulose wet gel film is subjected to solvent replacement to obtain a cellulose alcohol gel film; (2) placing the cellulose alcohol gel film obtained in step (1) in a homogeneous sol and allowing it to stand to obtain a cellulose / silicon composite wet gel; and subjecting the composite wet gel to aging and supercritical drying in sequence to obtain a transparent and flexible double-cross-linked silicon-based modified cellulose aerogel.

7. The method for preparing the transparent flexible double-crosslinked silicon-based modified cellulose aerogel according to claim 6, characterized in that: The reaction temperature for preparing the viscous liquid in step (1) is 100-140° C. and the reaction time is 4-48 h. The free radical initiator is one or more of di-tert-butyl peroxide, azobisisobutyronitrile or azobisisoheptylnitrile. The molar ratio of vinyl silane to free radical initiator is (5-15):

1.

8. The method for preparing the transparent flexible double-crosslinked silicon-based modified cellulose aerogel according to claim 6, characterized in that: The solvent in step (1) is one or more of methanol, ethanol, n-butanol or tert-butanol; the catalyst is one or more of tetramethylammonium hydroxide, ammonium fluoride or ammonia water; the molar ratio of methylsilane to solvent, deionized water and catalyst is 1:(1-5):(1-5):(0.01-0.1); the ionic liquid is one or more of EmimCl, EmimBr, EmimF, EmimAc, AmimCl, AmimBr or AmimF, and the mass fraction of the ionic liquid used for regeneration of the cellulose sol film is 20wt%; the cellulose sol film is prepared by mixing cellulose and the ionic liquid in a molar ratio of 1:(30-60).

9. The method for preparing the transparent flexible double-crosslinked silicon-based modified cellulose aerogel according to claim 6, characterized in that: The solvent replacement in step (1) is performed once every 12 hours, and the replacement is performed 2-4 times; the aging temperature in step (2) is 40-60° C., and the aging time is 12-48 hours; the supercritical drying is carbon dioxide supercritical fluid drying, the pressure is 5-20 MPa, the temperature is 30-60° C., and the drying time is 24-72 hours.

10. The use of the transparent flexible double-crosslinked silicon-based modified cellulose aerogel according to any one of claims 1 to 5, characterized in that: Used in thermal insulation field, as transparent glass interlayer.

Citation Information

Patent Citations

  • Preparation method of flexible transparent silicon-based modified cellulose aerogel film

    CN117126449A

  • Preparation method of hydrophilic-oleophobic cellulose / silane coupling agent composite aerogel

    CN110437493A

  • Biomass fiber hybrid polysiloxane aerogel glass and preparation method thereof

    CN111499919A

  • Preparation method of mechanically flexible cellulose aerogel with gradiently-changing wettability

    CN112321887A

  • Preparation method of nano cellulose aerogel composite fabric

    CN112411187A